The Presence of Popular Heritage in Social Media Networks (مجلة إحالات, 2026)
The folklore heritage plays a vital role in the cultural life of the nations and their history, since it reflectsthe nation's identity throughout history. Therefore, this cultural diversity must be preserved by introducing itand discussing it in social media and mobile apps. This later has brought an artistic touch that preserves thenation's heritage from being marginalized in comparison with the rapid growth and development of media andcultural globalization. As a result, this study attempts to shed light on some aspects of the folklore such as: "popular saying " and " folk joke " in the digital platforms.